Mapping literary modernism : time and development - Quinones, Ricardo J. (Princeton, New Jersey : Princeton University Press, 1985)
Professor Quinones describes significant stages in the development of literary Modernism, redefining the period as extending from about 1900 to 1940, and beyond, and not as an entity centered on the 1920s. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Prince.
Frontmatter -- Contents -- Acknowledgments -- Introduction -- I. The Collapse of Historical Values -- II. The Family, the Machine and the Paradox of Time -- III. Transformations -- IV. The Modernist Sensibility -- V. 'The Songs That I Sing" -- VI. Three Major Works -- VII. The Bite of Time -- CONCLUSION: Purviews and Purposes -- Notes -- Index
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Modernism (Literature); Literature, Modern -- 20th century -- History and criticism; Modernisme (Littérature); Littérature -- 20e siècle -- Histoire et critique; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; LITERARY CRITICISM -- General; Literature, Modern; Modernism (Literature); 1900-1999; Criticism, interpretation, etc